The Semantic Field of Love and Fear in Three Older and the Latest Slovene Translation of Deuteronomy - Avsenik Nabergoj, Irena (Slavia Centralis, 2023)
The paper is the result of a comparative analysis of selected Slovenian translations of all the passages of the Book of Deuteronomy in which the semantic field of love and fear is at the forefront. The comparison includes the Hebrew original, the two most influential ancient and three older Slovenian translations of the Bible, namely the translation by Jurij Japelj (1744–1807), the unpublished translation by Matevž Ravnikar (1776–1845) and the translation by Jurij Volc in the so-called Wolfʼs Bible (1805–1885). A comparative analysis of language and style in relation to the Hebrew original, the Greek Septuagint and the Latin Vulgate reveals similarities and differences in the older three and in the latest Slovenian translation of the Bible (SPJ) in terms of the use of vocabulary, the form of parallelism and the parenetic style. The focus is on how in Deuteronomy the lexeme “love” is linked to the lexeme “fear”, which is often only apparently opposed to the concept of love. We want to know whether these two concepts are exclusive or complementary in Deuteronomy. This paper provides important insights into the cognitive and emotional content of the concepts of “love” and “fear” in the Hebrew and Slovenian translations of Deuteronomy.